A Simultaneous Equation Model of Birth Rates in the United States - Gregory, Paul R.; Campbell, John M.; Cheng, Benjamin S. (The Review of Economics and Statistics, 1972)
Paul R. Gregory, John M. Campbell, Benjamin S. Cheng, A Simultaneous Equation Model of Birth Rates in the United States, The Review of Economics and Statistics, Vol. 54, No. 4 (Nov., 1972), pp. 374-380